Promosi Penjualan Jaket Thrift Branded Murah di Instagram - Khailla Putri Hasna Hanin; Indri Rachmawati (Bandung Conference Series: Communication Management, 2022)
Abstract. This research is entitled "Sales Promotion for Cheap Branded Thrift Jackets on Instagram (case study on the @bestlookingstuff account) "Thrift or Thriftingis an activity of buying and selling used goods that are still suitable for use, both well-known and not well-known brands. This study was made with the aim of knowing the sales promotion strategy in a business, especially the sale of cheap Thrift Branded jackets on Instagram @bestlookingstuff by looking at the supporting and inhibiting factors. The sales promotioncarried out by @bestlookingstuff is with free shipping for every purchase of 2 jackets, sales promotions are carried out by doing promotions on other Instagram accounts that also sell Thrift goods by having many followers and the owner of this @bestlookingstuff account pays to be promoted according to the price determined by the owner of the Instagram account in question, @bestlookingstuff also carries out promotions with IG Ads which can increaseits reach widely so that the @bestlookingstuff account is widely known by people, by purchasing 4 jackets, buyers will also get gifts from the owner of this @bestlookingstuff account. A business in this day and age has used several platforms available both on the PlayStore and on the AppStore. This research uses a qualitative research method with case studies. The data used are interviews, observations, and documentation with the owner of the Thrift @bestlookingstuff jacket business account by using additional data through several previous books and journals related to this research. The results of this study are that with a sales promotion carried out, a business will run well and according to the desired goal, it will also make this @bestlookingstuff account famous for its wide reach and many loyal customers to buy its Thrift jacket. Abstrak. Penelitian ini berjudul “Promosi Penjualan Jaket Thrift Branded Murah di Instagram ( studi kasus pada akun @bestlookingstuff ) “Thrift atau Thriftingini merupakan suatu kegiatan jual beli barang bekas yang masih layak pakai, baik itu bermerek terkenal maupun tidak terkenal. Penelitian ini dibuat bertujuan untuk dapat mengetahui strategi promosi penjualan pada suatu usaha khususnya penjualan jaket Thrift Branded yang murah di Instagram @bestlookingstuff dengan melihat faktor pendukung dan faktor penghambatny dan juga dengan melihat. Promosi penjualan yang dilakukan oleh @bestlookingstuff ini adalah dengan adanya gratis ongkir setiap pembelian 2 buah jaket, promosi penjualan dilakukan dengan melakukan promosi di akun Instagram lain yang juga menjual barang Thrift dengan memiliki pengikut yang banyakdan pemilik akun @bestlookingstuff ini membayar untuk dapat di promosikan sesuai dengan harga yang telah ditentukan oleh pemilik akun Instagram yang bersangkutan, @bestlookingstuff juga melakukan promosi dengan IG Ads yang dapat menambah jangkauan secara luas agar akun @bestlookingstuff banyak dikenal orang, dengan pembelian 4 jaket juga pembeli akan mendapatkan hadiah dari pemilik akun @bestlookingstuff ini. Sebuah usaha pada zaman sekarang ini sudah banyak menggunakan beberapa platform yang tersedia baik di PlayStore maupun di AppStore. Penelitian ini menggunakan sebuah metode penelitian kualitatif dengan studi kasus. Data yang digunakan adalah melakukan wawancara, observasi, dan dokumentasi dengan pemilik akun usaha jaket Thrift @bestlookingstuff dengan mengunakan tambahan data melalui beberapa buku dan jurnal terdahulu yang berhubungan dengan penelitian ini. Hasil dari penelitian ini yaitu dengan adanya promosi penjualan yang dilakukan maka sebuah bisnis akan berjalan dengan baik dan sesuai tujuan yang diinginkan, juga akan membuat akun @bestlookingstuff ini terkenal dengan jangkauan yang luas dan memiliki banyak pelanggan yang setia untuk membeli jaket Thrift nya.